Analysis of Customer Relationship Management Implementation in Maintaining Customer Loyalty in UMKM Bakpia Ahmad's Family Trenggalek - Tita Elma Sari; Siswahyudianto Siswahyudianto (Madani: Jurnal Politik dan Sosial Kemasyarakatan, 2023)
Bakpia Ahmad's Family is a company engaged in the food production sector. Bakpia in the form of food or cake with the basic ingredients of wheat flour, currently this food is widely known by the public. The emergence of other companies producing the same type of goods encourages the improvement of strategies to face competition and maintain customer loyalty for the continuity of the company's operations. To maintain customer loyalty, a Customer Relationship Management (CRM) strategy is implemented to realize the company's goals. CRM is a strategy used in business to manage and improve the quality of good relationships with customers. Establishing good relations with customers will create trust in the company. This study aims to analyze the implementation of Customer Relationship Management (CRM) in maintaining customer loyalty in Micro, Small and Medium Enterprises (MSMEs). This study uses a qualitative descriptive method with data collection techniques through interviews and observations of UMKM Bakpia Ahmad's Family in the city of Trenggalek. Data were analyzed using data condensation techniques, data presentation, and drawing conclusions. The results of the study show that the implementation of CRM is very important in maintaining customer loyalty to MSMEs. CRM helps MSMEs understand customer needs and preferences, and provides a good and consistent experience. In practice, MSMEs can implement CRM through several stages, namely acquiring new customers, retaining existing customers, and growing the most profitable customers.